1997
DOI: 10.1192/bjp.170.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Amisulpride versus placebo in the medium-term treatment of the negative symptoms of schizophrenia

Abstract: Amisulpride is effective in the medium-term treatment schizophrenic patients with predominantly negative symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(91 citation statements)
references
References 7 publications
3
87
0
1
Order By: Relevance
“…6 patients with acute exacerbations of schizophrenia have shown that amisulpride is as effective as haloperidol and flupenthixol in treating positive symptoms (Möller et al 1997;Puech et al 1998;Wetzel et al 1998) with additional effects on negative symptoms compared with haloperidol (Möller et al 1997). Amisulpride significantly reduces negative symptoms in patients with chronic schizophrenia presenting with enduring predominant negative symptoms (Boyer et al 1995;Loo et al 1997;Danion et al 1999) and in neuroleptic naive mainly negative schizophrenics at the onset of the disorder (Paillère-Martinot et al 1995). The efficacy of amisulpride was maintained in an open long-term study, with a clear advantage over haloperidol in terms of safety and efficacy (Colonna et al 2000).…”
mentioning
confidence: 99%
“…6 patients with acute exacerbations of schizophrenia have shown that amisulpride is as effective as haloperidol and flupenthixol in treating positive symptoms (Möller et al 1997;Puech et al 1998;Wetzel et al 1998) with additional effects on negative symptoms compared with haloperidol (Möller et al 1997). Amisulpride significantly reduces negative symptoms in patients with chronic schizophrenia presenting with enduring predominant negative symptoms (Boyer et al 1995;Loo et al 1997;Danion et al 1999) and in neuroleptic naive mainly negative schizophrenics at the onset of the disorder (Paillère-Martinot et al 1995). The efficacy of amisulpride was maintained in an open long-term study, with a clear advantage over haloperidol in terms of safety and efficacy (Colonna et al 2000).…”
mentioning
confidence: 99%
“…We made a sensitivity analysis excluding studies that consisted of patients with predominantly negative symptoms, [18][19][20][21][22][23] long-term studies on initially stable patients [24][25][26][27][28] and one very short study of only 2 weeks duration. 29 Owing to space limitations, we do not show the results here, but any result that deviated to an important extent from the primary analysis will be mentioned.…”
Section: Meta-analytic Calculationsmentioning
confidence: 99%
“…Two trials (Danion 1998, 60 Carriere 2000 47 ) were of medium duration -3-4 months, two trials lasted for 6 months (Lecrubier 1999, 42 Lecrubier 2000 43 ), with the remaining three trials (Colonna 1998, 49 Loo 1997, 63 Speller 1997 59 ) being of 1 year's duration (Loo 1997 was run initially for 6 months with 141 participants, then extended to 12 months for those patients who responded to treatment).…”
Section: Duration Of Studiesmentioning
confidence: 99%
“…At least nine trials (Colonna 1998, 64 Danion 1998, 60 Loo 1997, 63 Moeller 1997, 65 Martinot 1995, 52 Puech 1998, 56 Speller 1997, 59 Fleurot 1997, 62 Carriere 2000 47 ) were carried out or sponsored by Synthelabo, the manufacturers of amisulpride. Nine studies were published only as conference abstracts (including the amisulpride versus risperidone and olanzapine studies) and many methodological details are missing from these reports.…”
Section: Total Rctsmentioning
confidence: 99%
See 1 more Smart Citation